Conceptual provisions for increasing the level of economic efficiency of energy saving in construction enterprises - Glybovets, N. (Ways to Improve Construction Efficiency, 2018)
The article presents the genesis of the emergence of the first energy-efficient houses and considers the specificity of their application. The energy saving standards in the construction industry, the laws adopted in the EU countries, which are the basis for work in other countries, are also studied. The paper also gives examples of how to resolve the issue of motivating management companies in their energy-saving activities.